Teatar, svečanost, igre: misao Branka Gavelle - Čale-Feldman, Lada (2007)
The lecture presents and discusses one of Gavella's unpublished manuscripts, the one concerning Dubrovnik summer festival, in which this theoretician offers a broadened, anthropological approach to the phenomenon of acting as the building block of theatre's social relevance.